2020
DOI: 10.1177/2055217320964505
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of tolerability and effects on immunoglobulin levels and CD19 cell counts with ocrelizumab vs low dose of rituximab in multiple sclerosis

Abstract: Background Rituximab (RTX) and ocrelizumab (OCR) are two anti-CD20 biologics used in MS; however, comparisons on safety and efficacy are rare. Objective To compare treatment outcomes over the first year with RTX and OCR. Methods Retrospective cohort study comprising MS patients initiating RTX at the Karolinska University Hospital (Sweden; n = 311) and OCR at Rocky Mountain MS Clinic (Utah, USA; n = 161), respectively. Results Levels of immunoglobulin G measured in blood dropped 0.16 g/L (95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…In addition, dosing intervals had been extended already before the start of the pandemic, explaining why a proportion of patients had dosing intervals in the range of 9-24 months or more. However, the observations that cellular immunological responses were not affected by depletion status or time since last dose and that pwMS on the more potent B cell depleting OCR dosing regimen also displayed an adaptive response suggest that the results of the current study can be extrapolated to other doses of RTX and other anti-CD20 therapies (Evertsson et al, 2020). A further finding of our study is that the proportion of pwMS that tested positive for SARS-CoV-2 in the routine antibody test (ECLIA; 4.5%) is lower than the 11.6% seropositive prevalence reported in healthy blood donors by the Public Health Agency of Sweden for the Stockholm population already in June 2020 (https://www.folkhalsomyndigheten.se/contentassets/ 376f9021a4c84da08de18ac597284f0c/pavisning-antikroppar-genomgangen-COVID-19-blodgivare-delrapport-2.pdf).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, dosing intervals had been extended already before the start of the pandemic, explaining why a proportion of patients had dosing intervals in the range of 9-24 months or more. However, the observations that cellular immunological responses were not affected by depletion status or time since last dose and that pwMS on the more potent B cell depleting OCR dosing regimen also displayed an adaptive response suggest that the results of the current study can be extrapolated to other doses of RTX and other anti-CD20 therapies (Evertsson et al, 2020). A further finding of our study is that the proportion of pwMS that tested positive for SARS-CoV-2 in the routine antibody test (ECLIA; 4.5%) is lower than the 11.6% seropositive prevalence reported in healthy blood donors by the Public Health Agency of Sweden for the Stockholm population already in June 2020 (https://www.folkhalsomyndigheten.se/contentassets/ 376f9021a4c84da08de18ac597284f0c/pavisning-antikroppar-genomgangen-COVID-19-blodgivare-delrapport-2.pdf).…”
Section: Discussionmentioning
confidence: 78%
“…Beyond this, authors generally concluded that there were no relationships between baseline demographics and infection risk [ 52 , 55 ], and though an overall and pre- and post-treatment decline in IgG was seen in one study, conclusions couldn’t be drawn as to the relationship of these findings with risk of infection [ 52 ]. Finally, in a comparison of the tolerability and immune effects of ocrelizumab and rituximab in MS [ 58 ], reductions in IgG levels in ocrelizumab-treated patients and IgM levels in both groups were seen, but the significance of these findings with respect to infection was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported serious AEs (SAEs) are serious infections, followed by neoplasms. Treatment with Bcell-depleting anti-CD20 frequently results in a decrease in total immunoglobulins (IgG, IgM, IgA), typically associated to the occurrence of recurrent or complicated serious infections (45,46,(48)(49)(50)(51). As of December 2020, 10 cases of progressive multifocal leukoencephalopathy (PML) (nine cases had prior exposure to either natalizumab or fingolimod, and one case had no prior exposure (52), and six other serious opportunistic infections (including systemic Pasteurella infection, multisegmental herpes zoster infection, enterovirus-induced fulminant hepatitis requiring a liver transplant, Candida sepsis, viral meningitis) have been reported (44).…”
Section: The Role Of Anti-cd20 In Msmentioning
confidence: 99%
“…The most common AEs associated with the use of ocrelizumab are infections followed by infusion-related reactions (IRRs) ( 44 ). One observational study reported a higher risk of AE-related discontinuations for ocrelizumab versus rituximab (rate ratio [RR], 2.66; 95% confidence interval [CI], 1.09-6.47) ( 45 ). Current recommendations to reduce the risk of an IRR include pre-medication with intravenous methylprednisolone and an antihistamine and monitoring of patients during and after the infusion ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation